Guinea : Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2004)
In this paper, the following statistical data are listed in detail: economic and financial indicators, consumer price index, financial operations of the central government, central government revenue and expenditure, monetary survey, sectoral distribution of credit, structure of interest rate, balance of payments, composition of merchandise exports and imports, summary accounts of central bank and deposit money bank, external public debt service, nominal exchange rates, executive exchange rates, quarterly distribution of credit by sector and maturity, medium- and long-term external public debt, and summary of tax system.